Inclusão no ensino superior: A percepção de docentes de uma instituição pública do interior do estado de São Paulo - Poker, Rosimar Bortolini [UNESP]; Valentim, Fernanda Oscar Dourado [UNESP]; Garla, Isadora Almeida [UNESP] (FapUNIFESP (SciELO), 2018)
In the last decade, the inclusive education movement has reached higher education and demanded changes in its conditions of access and permanence. In this context, the research sought to investigate and analyze the perception of university teachers about the inclusion process of students with disabilities. It was considered factors that could interfere with their perception, such as contact with students with disabilities, attitudes have taken in the classroom, knowledge about inclusion and also the support and support offered by the institution. It was based on the case study of the professors of the Faculty of Philosophy and Sciences (FFC), Unesp, Marília Campus / SP. The data collected from a questionnaire indicated that teachers have a favorable perception regarding the inclusion process; however, they recognize that their attitudes are flawed and their training in the area is incipient, which leads them to feel insecure and unprepared. The institution was also the focus of criticism by teachers.
Inclusion in higher education: The perception of teachers of a public institution in the interior of the state of São Paulo
Keywords: Attitude measures; Higher education institutions; Inclusive Education